Pertanian Organik dan Pengaruhnya Terhadap Sifat Kimia Tanah dan Produksi Padi - Aisyah, Aisyah; BUDIANTA, DEDIK; SALAMPESSY, MESSALINA L (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2019)
Climate change greatly influences agricultural activities carried out by farmers in Indonesia. Farmers have begun to actively engage in organic farming, which is one of the production methods that is environmentally friendly, so that it can guarantee ecological sustainability. For this reason the study was conducted to determine the extent to which organic farming practices carried out by farmers can have implications for improving soil chemical properties and rice production. The method of this research is carried out by taking soil samples by surveying rice fields that apply organic systems and conventional systems. Data analysis using t test with a confidence level of 95%. The results showed that there were improvements in several soil chemical properties which included: organic C, total N, P available, K-dd and Al-dd soil, but improved soil chemical properties that were not significantly different from soil ph and soil CEC . To improve rice production, rice glucose content, root length, root volume and root dry weight there were significant improvements. Analysis of organic farming practices is important to limit the occurrence of all forms of environmental pollution that may be produced by conventional agricultural activities.